Risk management of selected risk categories and its effect on performance of commercial real estate properties in Kenya - Mbugua, James K; Otuya, Robert (International Journal of Entrepreneurship and Project Management, 2020)
Real estate is defined as land, including the air above it and the ground below it, and any buildings or structures on it. It covers residential housing, commercial offices, trading spaces such as theatres, hotels and restaurants, retail outlets, industrial buildings such as factories and government buildings. Real estate involves the purchase, sale, and development of land, residential and non-residential buildings. Due to its unique nature, heavy capital involvement and complexity, its development entails a lot of uncertainties and risks. Entrepreneurs in this sector are expected to make sound decisions in the management of these risks in order to achieve their entrepreneurial objective on property performance. Real estate sector is globally regarded as an integral partof a country’s economy. It is responsible for a considerable part of its development investment with sizeable amount of economic growth through backward and forward linkages to a considerable number of ancillary industries and sectors. Its contribution to GDP in 2010 was 28% (US) and 28% in United Kingdom (Kongela, 2013) .The Indian real estate sector is one of the most globally recognized sectors. It is slated to grow at 30 per cent over the next decade. The construction industry ranks third among the 14 major sectors in terms of direct, indirect and induced effects in all sectors of the economy (Kimani and Memba, 2017). The GDP share of real estate in India was 6.3 per cent in 2013 and expected to generate 7.6 million jobs a year. In China, the GDP share of real estate grew from 5 per cent in 2000 to 15 per cent in 2012, with 14 per cent of urban employment coming from real estate and related sectors (Mutreja, Chua and Guha, 2015). Similar performance were realized by African states were real estate contribution to GDP was6.82% (Nigeria in 2014), 10.2% (Tanzania in 2012) while in Kenya it registered 4.8% of GDP in the year 2013 (Kongela, 2013; Kenya National Bureau of Statistics (KNBS), 2015. Although, this sector plays a pivatol role in economic development, the performance of real estate properties has perinnially been eclipsed by several challenges including the management of its risks borne throughtout their development life cycle. The resultant is a threat to its expected or intended performance (Wiegelmann (2012).
Keywords: Risk management; entrepreneurship; risk factors; performance; commercial real estate properties.